Use of lectins to in situ visualize glycoconjugates of extracellular polymeric substances in acidophilic archaeal biofilms. Issue 3 (9th December 2014) - Zhang, R. Y.; Neu, T. R.; Bellenberg, S.; Kuhlicke, U.; Sand, W.; Vera, M.
Summary Biofilm formation and the production of extracellular polymeric substances (EPS) by meso‐ and thermoacidophilic metal‐oxidizing archaea on relevant substrates have been studied to a limited extent. In order to investigate glycoconjugates, a major part of the EPS, during biofilm formation/bioleaching by archaea on pyrite, a screening with 75 commercially available lectins by fluorescence lectin‐binding analysis (FLBA) has been performed. Three representative archaeal species, Ferroplasma acidiphilum DSM 28986, Sulfolobus metallicus DSM 6482T and a novel isolate Acidianus sp. DSM 29099 were used. In addition, Acidianus sp. DSM 29099 biofilms on elemental sulfur were studied. The results of FLBA indicate (i) 22 lectins bound to archaeal biofilms on pyrite and 21 lectins were binding to Acidianus sp. DSM 29099 biofilms on elemental sulfur; (ii) major binding patterns, e.g. tightly bound EPS and loosely bound EPS, were detected on both substrates; (iii) the three archaeal species produced various EPS glycoconjugates on pyrite surfaces. Additionally, the substratum induced different EPS glycoconjugates and biofilm structures of cells of Acidianus sp. DSM 29099. Our data provide new insights into interactions between acidophilic archaea on relevant surfaces and also indicate that FLBA is a valuable tool for in situ investigations on archaeal biofilms.